2020
DOI: 10.1007/s00253-020-10706-9
|View full text |Cite
|
Sign up to set email alerts
|

A universal polyphosphate kinase: PPK2c of Ralstonia eutropha accepts purine and pyrimidine nucleotides including uridine diphosphate

Abstract: Polyphosphosphate kinases (PPKs) catalyse the reversible transfer of the γ-phosphate group of a nucleoside-triphosphate to a growing chain of polyphosphate. Most known PPKs are specific for ATP, but some can also use GTP as a phosphate donor. In this study, we describe the properties of a PPK2-type PPK of the β-proteobacterium Ralstonia eutropha. The purified enzyme (PPK2c) is highly unspecific and accepts purine nucleotides as well as the pyridine nucleotides including UTP as substrates. The presence of a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Purified PPK proteins (1-4 mg/ml) were stored on ice directly in elution buffer (pH 8.0 (composition see below) without any further treatment (250 mM imidazole, 300 mM NaCl and 50 mM NaH 2 PO 4 ). PPK activity assays and reaction product determination via HPLC were performed as described in detail previously (Hildenbrand et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purified PPK proteins (1-4 mg/ml) were stored on ice directly in elution buffer (pH 8.0 (composition see below) without any further treatment (250 mM imidazole, 300 mM NaCl and 50 mM NaH 2 PO 4 ). PPK activity assays and reaction product determination via HPLC were performed as described in detail previously (Hildenbrand et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Targeted LC-MS measurements were performed with enhanced sensitivity on an Agilent 1200 HPLC system coupled with an Agilent 6410B triple quadrupole mass spectrometer (QQQ). Sample preparation and chromatographic separation of nucleoside phosphates by bicratic polymer-based zwitterionic hydrophilic interaction chromatography (ZIC-pHILIC) were performed as previously described (Feith et al 2019;Hildenbrand et al 2020) with following modifications: Mobile phases (constant flow rate of 0.2 ml min −1 ) were composed of aqueous buffer solutions (10 mM ammonium acetate, pH 9.2) with 90% (v/v) acetonitrile for eluent A and 10% (v/v) acetonitrile for eluent B, using the following program for gradient elution: isocratic hold 0% B for 1 min, linear gradient from 0% B to 70% B for 19 min, linear gradient from 70% B to 100% B for 2 min, isocratic hold 100% B for 2.5 min, linear gradient from 100% B to 0% B for 4 min, and equilibration to starting conditions by an isocratic hold 0% B for 12 min. Nucleoside mono-, di-, and triphosphates were detected in negative ionization mode (ESI-) with high sensitivity in selected ion monitoring (SIM) mode based on pre-optimized precursor ion transitions with a mass resolution of 0.3 u and associated MS parameters (Teleki et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of PPK2 enzymes side activities, the metal dependent adenylate kinase activity (2 ADP⇔ATP+AMP) of several PPK2s was recently demonstrated by functional and structural studies [19,35] . Moreover, the phosphorylation of AMP beyond ATP to form adenosine 5’‐tetraphosphate (A4P) and adenosine 5’‐pentaphosphate (A5P) by PPK2 enzymes was exemplified and supported by structural studies [23,31,35,37] …”
Section: Polyphosphate Kinases‐2: Biochemical Featuresmentioning
confidence: 93%
“…Nucleotide preference analysis of PPK3 from Ruegeria pomeroyi and PPK2c from Ralstonia eutropha (phylogenetically related to PPK2‐I enzymes) revealed that these enzymes have a broad substrate scope, being able to accept both purine and pyrimidine nucleotide diphosphates [23–24] . While the former displayed a two‐fold higher phosphorylation activity with CDP/UDP compared to that with ADP/GDP, the latter had similar activity against ADP, GDP, CDP, dTDP and UDP.…”
Section: Polyphosphate Kinases‐2: Biochemical Featuresmentioning
confidence: 99%